PERAN KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI TERHADAP KINERJA KARYAWAN DENGAN MODERASI MASA KERJA - Noermijati Noermijati (University of Merdeka Malang, 2015)
Leadership had a critical role for banking organization to enhance employee performance. In addition, organizationhad to pay more attention to employee's work motivation and tenure. The research purposes were toanalyze the effect of transformational leadership and work motivation on employee performance, and the roleof tenure to moderate the effect of transformational leadership and work motivation on employee performance.This research involved 100 operational employees as the respondents with simple random sampling technique.By using Moderation regression analysis, it was found that transformational leadership significantlyinfluenced employee performance. However, work motivation did not influence employee performance. Tenuremoderated the role of transformational leadership on employee performance; meanwhile, tenure did not moderatedthe effect of work motivation on employee performance of BRI Bank, Jombang branch.